Priority-based constructive algorithms for scheduling agile earth observation satellites with total priority maximization - Xu, Rui; Chen, Huaping; Liang, Xinle; Wang, Huimin (Expert systems with applications, 2016)
•We study an Earth observation scheduling problem from China’s satellite platform.•We develop priority-based indicators based on a cost-benefit analysis method.•We employ a sequential construction procedure to generate feasible solutions.•We evaluate the performance of the proposed algorithms in various scenarios. This paper investigated an Earth observation scheduling problem for agile satellites under a time window constraint and resource constraints of limited on-board memory capacity and consecutive working time. We assumed that different observation tasks may have priority levels, and the objective is to maximize the total priority of selected tasks. To address the problem, we first presented a detailed problem description and developed a mathematical programming model. Considering the over-constrained feature of the problem, we developed constructive algorithms to solve the problem, which adopt a priority-based sequential construction procedure to avoid conflicts and generate feasible solutions. The proposed sequential construction procedure contributes to eliminating the need for extra constraint handling techniques, and helps to reduce the complexity of feasibility checking. By analyzing the competitive relationship of various resources, we proved the condition of mutual exclusion of time windows and then developed new priority-based indicators to evaluate the benefits and opportunity costs of different positioning decisions, which is a key component to be used in the proposed constructive algorithms. Through extensive computational experiments on various scenarios including real-world data from China’s satellite platform, the effectiveness of the developed constructive algorithms was verified.